Temporal dysregulation of genes in lamb testis cell during sheeppox virus infection. (1st December 2022) - Sonowal, J.; Patel, C.L.; Gandham, R.K.; Khan, R.I.N.; Praharaj, M.R.; Malla, W.A.; Dev, K.; Barkathullah, N.; Bharali, K.; Dubey, A.; Singh, N.; Mishra, B.P.; et al.
Abstract: The present study was aimed to elucidate the host–virus interactions using RNA‐Seq analysis at 1 h and 8 h of post‐infection of sheeppox virus (SPPV) in lamb testis cell. The differentially expressed genes (DEGs) and the underlying mechanisms linked to the host immune responses were obtained. The protein–protein interaction (PPI) network analysis and ingenuity pathway analysis (IPA) illustrated the interaction between the DEGs and their involvement in cell signalling responses. Highly connected hubs viz. AURKA, CHEK1, CCNB2, CDC6 and MAPK14 were identified through PPI network analysis. IPA analysis showed that IL‐6‐ and ERK5‐mediated signalling pathways were highly enriched at both time points. The TP53 gene was identified to be the leading upstream regulator that directly responded to SPPV infection, resulting in downregulation at both time points. The study provides an overview of how the lamb testis genes and their underlying mechanisms link to growth and immune response during SPPV infection. Abstract: Significance and Impact of Study: The host cellular processes, particularly the immune response, are highly influenced during virus infection. Previously, we have conducted a transcriptomics study of the sheeppox virus (SPPV) infection in lamb testis cell during the immediate‐early (0·5 h) phase when only the immediate‐early pox viral genes are expressed. However, the SPPV expresses its early genes within 1–2 h and late genes within 8 h in the cell cytoplasm, both of which in turn affect the expression of the host genes. These host–pathogen interactions tend to activate various cell signalling pathways involved in several cellular processes.